Mechanisms of discourse comprehension impairment after right hemisphere brain damage: suppression in lexical ambiguity resolution. - Tompkins, Connie A.; Baumgaertner, Annette; Lehman, Margaret T. (Journal of Speech, Language & Hearing Research, 2000)
Normal comprehension skill is linked with the proficiency of a suppression mechanism, which functions to dampen mental activation that becomes irrelevant or inappropriate to a final interpretation. This study investigated suppression and discourse comprehension in adults with right brain damage (RBD). To index suppression function, 40 adults with RBD and 40 without brain damage listened to sentence stimuli that biased the meaning of a sentence-final lexical ambiguity (e.g., SPADE), then judged whether a probe word (e.g., CARDS) fit the overall sentence meaning. Probes represented the contextually inappropriate meanings of the ambiguities and were presented in two conditions: 175 ms and 1000 ms post-stimulus. The same probes were used with unambiguous comparison stimuli. Probe judgment response times indicated that only the group without brain damage suppressed inappropriate interpretations over time. In a multiple regression analysis, suppression function added significantly to predicting performance on a general measure of narrative discourse comprehension for participants with RBD. The discussion addresses how suppression deficits may account more broadly for comprehension difficulties after RBD; it also considers several unresolved issues concerning the suppression construct and the suppression deficit hypothesis. Reprinted by permission of the publisher. Reprinted by permission of the publisher.